The chronicles of medical libraries in Malaysia - Persatuan Pustakawan Malaysia (Malaysian Medical Librarian Group, 2022)
The Medical Librarians Group (MLG) promotes excellence and leadership of health information professionals through education, communication and resource sharing by utilizing the information systems and services, cooperation and networking among member libraries in support of informed health care decision making.